(3GdEbJVGH aj TQM COH GdcJGHs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s ((3RjO Hf CMeO GdefUhQ s)
(3ChdgG (B:s
(3GdMeO ddg ehRY GdMeO hedgeg bGd YHOGddg Hf eMeO Hf GdSjO GdHWdjhSj(B: (3ZQVj ef cJGHj gPG JaSjQ NWHI GdcJGH GdehShe HCOH GdcJGH hPcQ CUfGa GdcJHI heQGJHge s
(3BNQgG (B:s
(3hbO PcQJ ajeG JbOe Cf GdQhGjI Yf CHj fUQ Yf CHj Ydj fbdJ EdjfG hCfTOg GHf Lfj HGdOGd ZjQ oeYLeI, hgh GdUhGH Cf TGA Gddg Je LejY GdcJGH HMeO Gddg hMSf Yhfg s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B50 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(503) s
Keywords: (3GdCOHs